Test Of Inhibitory Power Of Cotton Leaf Extract (Gossypium Hirsutum L.) As Anti Bacterial Staphylococcus Aureus - Fauzi, Ahmad Zil (Universitas Dehasen Bengkulu, 2023)
Utilization of natural ingredients as medicine tends to increase in recent times to replace modern medicines such as cotton leaves. Many plant species have antibacterial properties, including the cotton plant (Gossypium hirsutum L.). Cotton leaf plant (Gossypium hirsutum L.). It is known that natural compounds that have the potential as antibacterials generally contain saponins, alkaloids, polyphenols, and flavonoids are cotton plants (Gossypium hirsutum L.). Therefore, it is necessary to conduct research on the inhibition of Cotton leaf extract (Gossypium hirsutum L.) as an anti-bacterial agent for Staphylococcus aureus. The general objective of this study was to determine the effectiveness of cotton leaves (Gossypium hirsutum L.) as an antibacterial for Staphylococcus aureus. The results of this study are expected to provide basic information about the use of cotton leaves (Gossypium hirsutum L.) as an alternative treatment for infectious diseases, especially those caused by Staphylococcus aureus bacteria so that they can become one of the efforts to develop treatments derived from natural ingredients. This type of research is a laboratory experimental design with a one shoot case study design, namely a research design with treatment of the independent variables followed by observations or measurements of the independent variables. Based on the data from this study it can be concluded that cotton leaf extract (Gossypium hirsutum L.) is able to inhibit the growth of Staphylococcus aureus, with a sensitive category where the greatest antibacterial activity is produced at an extract concentration of 100% which is indicated by the formation of an inhibition zone of 18.10 mm.